Assessment of Responsible Innovation : Methods and Practices. - Yaghmaei, Emad.; Poel, Ibo van de. (Milton : Taylor & Francis Group, 2020)
Brings together many of the leading researchers and thinkers in the field of RRI to present the most comprehensive review of RRI assessment tools.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books